Wipro's Geographical Model Transition: A Deep Dive Across Phases - Nanda Kishore Shetty, Umasaikiran Minnakuri, Prajwal P, (European Economic Letters (EEL), 2024)
This study explores Wipro Limited's strategic transition from a sector-wise sales and distribution model to a geographical territory-based approach, initiated in 2022. Amidst a rapidly evolving global market landscape, this shift represents a pivotal reorientation in Wipro's operational and strategic frameworks aimed at harnessing enhanced client engagement, localized market penetration, and streamlined operations. Through an exhaustive three-phase research methodology encompassing pre-implementation analysis, implementation dynamics, and post-implementation outcomes, this paper sheds light on the myriad challenges, strategic pivots, and the consequent impacts of this transition on sales performance, marketing strategies, and customer satisfaction. This comprehensive exploration into Wipro's strategic shift not only contributes to the academic discourse on sales strategy transformation in the IT services sector but also offers practical insights for organizations contemplating similar geographical-centric restructurings.